Exosomes Isolated From Bone Marrow Mesenchymal Stem Cells Exert a Protective Effect on Osteoarthritis via lncRNA LYRM4-AS1-GRPR-miR-6515-5p - Wang, Xiuhui; Li, Zhuokai; Cui, Yin; Cui, Xu; Chen, Cheng; Wang, Zhe (Frontiers in Cell and Developmental Biology, 2021)
Objectives: The study was aimed to investigate the effects of exosomes isolated from human bone marrow mesenchymal stem cells (BMSCs) on osteoarthritis (OA), and a competitive endogenous RNA (ceRNA) network was further explored. Methods: Exosomes were isolated from human BMSCs, and characterized by transmission electron microscopy (TEM), Nanosight (NTA) and western blot. Chondrocytes was treated with interleukin-1β (IL-1β), and then transfected with exosomes. Afterwards, cell viability and apoptosis were determined by Cell Counting Kit-8 (CCK-8) and flow cytometer, respectively. The cells with IL-1β and with exosomes were both sequenced, and differentially expressed lncRNAs (DE-lncRNAs) and miRNAs (DE-miRNAs) were identified. Thereafter, a ceRNA network (LYRM4-AS1-GRPR-miR-6515-5p) was chosen for further validation, Results: TEM, NTA and western blot showed exosomes were successfully isolated, and PKH67 staining showed exosomes could be taken up by IL-1β-induced chondrocytes. Compared with the control group, IL-1β significantly decreased cell viability and promoted apoptosis (P < 0.05); while exosomes properly reversed the changes induced by IL-1β. For MMP3, AKT, and GRPR, IL-1β up-regulated their expressions; while exosomes down-regulated their expressions. For PTEN, There was no significant difference in PTEN expression between control and IL-1β groups; but exosomes markedly up-regulated its expression. By sequencing, a total of 907 DE-lncRNAs and 25 DE-miRNAs were identified, and a ceRNA network was built. Dual-luciferase reporter gene indicated LYRM4-AS1, miR-6515-5, and GRPR interacted with each other. The results of cell experiments showed LYRM4-AS1 regulated cell growth of IL-1β-induced chondrocytes by GRPR/miR-6515-5p. Conclusions: Exosomes may alleviate OA inflammation via regulating LYRM4-AS1/GRPR/miR-6515-5p signal pathway.